1988
DOI: 10.1164/ajrccm/137.4.820
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Cohort Study of Lung Cancer and Diesel Exhaust Exposure in Railroad Workers

Abstract: The risk of lung cancer as a result of exposure to diesel exhaust from railroad locomotives was assessed in a cohort of 55,407 white male railroad workers 40 to 64 yr of age in 1959 who had started railroad service 10 to 20 years earlier. The cohort was traced until the end of 1980, and death certificates were obtained for 88% of 19,396 deaths; 1,694 lung cancer cases were identified. Yearly railroad job from 1959 to death or retirement was available from the Railroad Retirement Board, and served as an index o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
177
1
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 194 publications
(187 citation statements)
references
References 5 publications
6
177
1
3
Order By: Relevance
“…Several epidemiologic studies have demonstrated an increased risk of lung cancer in persons occupationally exposed to diesel exhausts, for example, American railroad workers (Garshick et al 1987(Garshick et al , 1988 and Swedish dock workers (Emmelin et al 1993;Gustafsson et al 1986) and bus garage workers ). These studies have not yet provided quantitative risk estimates relative to PAHs.…”
Section: Epidemiologic Datamentioning
confidence: 99%
“…Several epidemiologic studies have demonstrated an increased risk of lung cancer in persons occupationally exposed to diesel exhausts, for example, American railroad workers (Garshick et al 1987(Garshick et al , 1988 and Swedish dock workers (Emmelin et al 1993;Gustafsson et al 1986) and bus garage workers ). These studies have not yet provided quantitative risk estimates relative to PAHs.…”
Section: Epidemiologic Datamentioning
confidence: 99%
“…[1][2][3][4][5] Inhalation of PM 10 particulate was studied because of a greater mortality rate during increased levels of air pollution. 6 Toxic particles might affect the human respiratory system because of their physical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…We derive our central and upper bound estimates for diesel's contribution to lung cancer incidence from the Dawson and Alexeeff (23) reanalysis of the Garshick et al (24) railroad worker study. Others have suggested that use of these data to estimate risk is inappropriate (25,26) and that the Dawson and Axeleeff finding reflects confounding (26).…”
Section: Atmospheric Dispersion and Populationmentioning
confidence: 99%